Effectiveness of Implementing a Management Control System for Revenue Increase via Credit Sales: A Map Analysis - Aisyah, Siti; Anindya, Desy; Habibie, Muhammad; Purnamasari, Eka (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research was conducted to determine and analyze the effectiveness of implementing a management control system in increasing income through credit sales at PT. Astra International, Gatot Subroto Medan Branch. The research method used is a qualitative approach, incorporating primary data obtained through interviews and secondary data from literature studies and documentation via the official company website and supporting documents requested directly from the source. The research results indicate that the management control system has not effectively increased income through credit sales at the distributor company. This is attributed to the sales and management department's failure to update the requirements for purchasing cars on credit, and the standard operating procedure (SOP) for credit sales has not been fully implemented. The distributor company faces obstacles in implementing a credit sales system, including a lack of cooperation between the company and the leasing party in facilitating credit approval, along with insufficient work motivation and limited time for evaluating improvements to the credit sales system. To address these challenges, the company endeavors to enhance revenue through the credit sales system by updating the requirements for purchasing cars on credit to attract customers. Additionally, the company conducts consistent monthly evaluations in accordance with the Standard Operation Procedure (SOP).